Tata Cahaya pada Selasar Sunaryo Art Space - Bandung - Setiowati, Erindiah; Saryanto, Saryanto (REKA JIVA, 2013)
Sunaryo Art SpaceErindiah Setiowati[Tata Cahaya pada Selasar Sunaryo Art Space – Bandung] -2AbstractInternal lighting is very important. Sources of light may come from natural or simulated sources. As in art galleries, lighting functions to support activities inside the gallery as they generally house the many art work of various artists, whether for safe-keeping or display. These include paintings, statues, and other works of art. The technical specifications for lighting in galleries covers the type, technique, and arrangement of lightings on each artwork and display. These include the luminence and flux needed to determine the amount of light required in a gallery, the influencing factors presented by the building itself, the artifacts itself, and form of display. The Selasar Sunaryo Art Space (SSAS) is an gallery which possesses the most complete facilities in Bandung. SSAS was built by Drs. Sunaryo, a prominent Indonesian artist who has produced many paintings and statues, and has received many awards in the field of art. SSAS was built in 1998. In addition to conducting activities related to contemporary art, the gallery also displays Sunaryo's works of art as well as of other artists wishing to exhibit their works. SSAS was selected as object for this study because of its uniqueness. The gallery uses natural lighting for most of its displays by using many glass windows along the walls of its display rooms. SSAS is also used to exhibit other forms of art work and its flexible lighting can be adjusted to various purposes.Key Word: Lighting, Art Gallery, Selasar Sunaryo Art Space.